AMPUTATION OF CERVIX AND NEOCERVIX CREATION USING STURMDORF TECHNIQUE IN RECURRENT CERVICAL SARCOMA BOTRYOIDES: A CASE REPORT - Pribakti Budinurdjaja; Ihya Ridlo Nizomy; Inas Tsurayya Fauziah Lahdimawan (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstract: Sarcoma botryoides, or embryonal rhabdomyosarcoma, is soft tissue sarcoma arises from embryonic muscle cells and normally present with discharge, bleeding, or a visible mass at the vaginal introitus in infants and children. Aim of this study is to report a case of cervical sarcoma botryoides. Method used is a Case report. A 16-year-old girl, nulliparous, complained abnormal vaginal bleeding and a protruding vaginal mass. Patient underwent first surgery, mass recurrent five months later. The second surgery was performed by cervical amputation and neocervix creation using Sturmdorf sutures technique. Postoperative week 12 demonstrated a healthy neocervix in appearance, her menses have resumed, indicated patency. She has no evidence of disease 3 months after diagnosis. Cervical sarcoma botryoides is a rare malignancy. Clinicians must thoroughly examine any polyp or mass protrudes from vagina. Early diagnosis and treatment are essential for better prognosis. Sarcoma botryoides has a much improved prognosis with multimodality treatment. To determine the long-term survival and future potential fertility outcome, larger study and longer follow-up are needed. Keywords: sarcoma, botyroides, embryonal, rhabdomyosarcoma, neocervix